2021
DOI: 10.1186/s43141-021-00178-3
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of prognostic markers in acute pancreatitis: internist’s point of view

Abstract: Acute pancreatitis, the most frequent hospitalization reason in internal medicine ward among gastrointestinal diseases, is burdened by high mortality rate. The disease manifests mainly in a mild form, but about 20-30% patients have a severe progress that requires intensive care. Patients presenting with acute pancreatitis should be clinically evaluated for organ failure signs and symptoms. Stratifying patients in the first days from symptoms onset is essential to determine therapy and care setting. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies have observed a correlation between cardiac events and the severity of AP [ 6 ]. Various markers of cardiac injury have been linked to severe outcomes in patients with AP [ 9 , 15 , 21 , 24 ]. Raised levels of CK-MB have also been associated with higher mortality and development of severe AP, characterized by prolonged organ failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have observed a correlation between cardiac events and the severity of AP [ 6 ]. Various markers of cardiac injury have been linked to severe outcomes in patients with AP [ 9 , 15 , 21 , 24 ]. Raised levels of CK-MB have also been associated with higher mortality and development of severe AP, characterized by prolonged organ failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raised levels of CK-MB have also been associated with higher mortality and development of severe AP, characterized by prolonged organ failure [ 15 ]. On the contrary, NT-proBNP levels have shown mixed results in predicting severity and organ failure among patients with AP [ 24 ]. Raised levels of troponin T have also been associated with poor prognosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study enrolling 146 AP patients demonstrated that an increase in SOFA independently heightened the likelihood of adverse outcomes during hospitalization for AP patients, and SOFA > 5 was highly predictive of in-hospital mortality compared to other scores[ 135 ]. Utilizing a straightforward tool like SOFA, validated in intensive care settings, could enhance the stratification of in-hospital mortality risk and clinical deterioration among AP patients admitted to medical wards.…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%